Transaction cost and its effects towards outsourcing - Mustapa, Fara Diva; Hashim, Maizon (2006)
This paper explores the drawbacks of outsourcing which surfaces from the transaction costs. Coupled with the benefits to the host organisation are the drawbacks which include the information costs, negotiating and bargaining, and the costs of policing and enforcement. The paper is based on a case study carried out on the outsourcing of the healthcare support services by the Malaysian Ministry of Health. The case study attempts to generate an understanding on the causes of the significant increase in the operational costs of the abovesaid healthcare support services and relating it to transaction costs. Structured interviews were conducted on those directly involved in the planning, implementing and monitoring of the outsourcing process of the healthcare support services. The findings indicated that bounded rationality, opportunism and asset specificity are the main components of the transaction costs. However, the significant increase in the operational costs of the healthcare support services of the Malaysian Ministry of Health was not entirely due to the effects of the drawbacks of outsourcing.